Laparoscopic management of acute appendicitis in situs inversus - Golash, Vishwanath (Medknow Publications, 2006)
Situs inversus is often detected incidentally in adults during imaging for a acute surgical emergency. We present a case of acute appendicitis in an adult who was previously unaware about his situs anomaly. A laparoscopic approach is helpful to deal with this condition. A 40 year old man was admitted with history of acute left lower abdominal pain, with uncontrolled diabetic keto-acidosis. Clinically, he was diagnosed as acute diverticulitis with localized peritonitis. Subsequent imaging studies and laparoscopy confirmed the diagnosis of situs inversus and acute left- sided appendicitis. He successfully underwent laparoscopic appendectomy. His postoperative recovery was uneventful. Although technically more challenging because of the reverse laparoscopic view of the anatomy, the laparoscopic diagnosis and management of acute appendicitis is indicated in situs inversus.